Cross-Temporal Exploration of the Relationship Between Wisdom-Related Cognitive Broadening and Subjective Well-Being: Evidence From a Cross-Validated National Longitudinal Study. Issue 4 (May 2021) - Santos, Henri C.; Grossmann, Igor
How do intraindividual changes in wisdom-related characteristics of cognitive broadening—open-minded reflection on challenging situations, consideration of change, and epistemic humility—relate to subjective well-being over time? To test this relationship, we performed cross-lagged panel analyses from three waves of the national U.S. sample taken across 20 years, utilizing a cross-validation approach: (i) conduct exploratory analyses on a random subset of data, (ii) preregister hypotheses and methods, and (iii) cross-validate preregistered hypotheses on the other random subset of the data. We found that broadening attitudes predicted greater affect balance and life satisfaction in later years, but not vice-versa. The effect was robust when controlling for trait-level broadening well-being associations, as well as sociodemographic characteristics, openness, and general cognitive abilities. The direction of the positive longitudinal relationship between broadening attitudes and subjective well-being has implications for major existing theories of adult development and subjective well-being.